Preliminary estimates of growth and mortality in Nemipterus bathybus Snyder (Pisces: Nemipteridae) from the coast off Sarawak, South China Sea - Ambak, Mohd Azmi; Mohammad Mohsin, Abu Khair; Mohd Said, Mohd Zaki (Universiti Pertanian Malaysia, 1988)

(untitled)
Length-frequency samples of Nemipterus bathybus Snyder (Pisces: Nemipteridae) obtained in a trawl sU11ley off the coast of Sarawak, East Malaysia (South China Sea) were separated into components using the Bhattacharya method. The mean length of adjacent components. assumed to represent year classes, were used to estimate the parameters Loo and K of the von Bertalanffy equation, while the numbers of fisah in these components were used to estimate total mortality. Results were: TLoo = 31.2, K = 0.36 year-1 and Z =1.4 year -1. The results are discussed in relation to other estimates ofN. bathybus and other species of threadfin breams.